Strategi Pembelajaran IPA pada Peserta Didik dengan Menggunakan Metode Pembelajaran Project Based Learning (JPBL) - Chandra Sagul Haratua; Ike Ismawati; Syafira Setya Putri; Widiyantoro Widiyantoro (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Project-Based Learning is a learning model that uses projects as the core of learning (Permendikbud, 2014:20). This learning model is an innovative learning model that involves project work where students work independently in constructing their learning and culminating it in real products (Nanang Hanafiah and Cucu Suhana, 2009:30). Project Based Learning learning model is a learning strategy where students must build their own content knowledge and demonstrate new understanding through various forms of representation (NYC Department of Education 2009:8). characteristics of the PJBL Learning Model The Project Based Learning, learning model was developed based on the level of development of students' thinking, centered on students' learning activities so as to enable them to carry out activities according to their skills, comfort and learning interests. This model gives students the opportunity to determine for themselves the project they will work on, both in terms of formulating questions to be answered, choosing topics to research, and determining research activities to be carried out. The teacher's role in learning is as a facilitator, providing materials and work experience, encouraging students to discuss and solve problems, and ensuring students remain enthusiastic while they carry out the project. Keywords: project-based learning model